"Generalized‐to‐focal" epilepsy: stereotactic EEG and high‐frequency oscillation patterns. Issue 6 (9th January 2023) - von Ellenrieder, Nicolas; Dubeau, Francois; Dudley, Roy W.R.; Dufresne, David; Gotman, Jean; Baillet, Sylvain; Moreau, Jeremy T.; Bernasconi, Neda; Bernasconi, Andrea; Osterman, Bradley; Simard‐Tremblay, Elisabeth; Myers, Kenneth A.
Abstract: Objective . We aimed to clarify the pathophysiology of epilepsy involving seizures with apparently generalized onset, progressing to focal ictal rhythm through stereotactic EEG (SEEG) implantation, recording, stimulation and highfrequency oscillation (HFO) analysis. Methods . We identified two patients with seizures with bilateral electrographic onset evolving to focal ictal rhythm, who underwent SEEG implantation. Patients had pre‐surgical epilepsy work‐up, including prolonged video scalp EEG, brain MRI, PET, ictal/interictal SPECT, MEG, and EEG‐fMRI prior to SEEG implantation. Results . Both patients had childhood‐onset seizures involving behavioural arrest and left versive head and eye deviation, evolving to bilateral tonic‐clonic convulsions. Seizures were electrographically preceded by diffuse, bilateral 3‐Hz activity resembling absence seizures. Both had suspected focal lesions based on neuroimaging, including 3T MRI and voxel‐based post‐processing in one patient. Electrode stimulation did not elicit any habitual electroclinical seizures. HFO analysis showed bilateral focal regions with high fast‐ripple rates. Significance . "Generalized‐to‐focal" seizures may occur due to a diffuse, bilateral epileptic network, however, both patients showed ictal evolution from a generalized pattern to a single dominant focus which may explain why the focal aspect of their seizures had a consistent clinical semiology. Patients such as these may have a unique form of generalized epilepsy, but focal/multifocal cerebral abnormalities are also a possibility.